Drawing attention to metaphor case studies across time periods, cultures and modalities - Di Biase-Dyson, Camilla; Egg, Markus, 1963- (Figurative thought and language, 2020)
"The communicative act of drawing attention to metaphor is a relatively recent topic in metaphor studies and one that has remained contentious from a cognitive perspective. This book brings philologists of ancient languages together with metaphor experts from several modalities to interrogate whether ancient and modern texts and languages draw attention to figurative tropes in similar ways. In this way, the diachronic, multimodal and pluridisciplinary contributions to this volume critically review the theoretical frameworks underpinning metaphor marking and metaphor analysis from a completely new empirical basis"--